Taurine supplementation in conjunction with exercise modulated cytokines and improved subcutaneous white adipose tissue plasticity in obese women - De Carvalho, Flavia Giolo (2021)
Interventions that can modulate subcutaneous white adipose tissue (scWAT) function, such as exercise training and nutritional components, like taurine, modulate the inflammatory process, therefore, may represent strategies for obesity treatment. We investigated the effects of taurine supplementation in conjunction with exercise on inflammatory and oxidative stress markers in plasma and scWAT of obese women. Sixteen obese women were randomized into two groups: Taurine supplementation group (Tau, n = 8) and Taurine supplementation + exercise group (Tau + Exe, n = 8). The intervention was composed of daily taurine supplementation (3 g) and exercise training for 8 weeks. Anthropometry, body fat composition, and markers of inflammatory and oxidative stress were determined in plasma and scWAT biopsy samples before and after the intervention. We found that, although taurine supplementation increased taurine plasma levels, no changes were observed for the anthropometric characteristics. However, Tau alone decreased interleukin-6 (IL-6), and in conjunction with exercise (Tau + Exe), increased anti-inflammatory interleukins (IL-15 and IL10), followed by reduced IL1β gene expression in the scWAT of obese women. Tau and Tau + Exe groups presented reduced adipocyte size and increased connective tissue and multilocular droplets. In conclusion, taurine supplementation in conjunction with exercise modulated levels of inflammatory markers in plasma and scWAT, and improved scWAT plasticity in obese women, promoting protection against obesity-induced inflammation. TRN NCT04279600 retrospectively registered on August 18, 2019.